β2GPI-targeted polymeric nanoparticles form a protective layer to prevent vascular thrombosis in an anti-phospholipid syndrome model - Durigutto, Paolo; Grimaldi, Maria Cristina; Bozzer, Sara; Raschi, Elena; Meroni, Pierluigi; Tedesco, Francesco; Macor, Paolo (Frontiers in Immunology, 2025)
Anti-phospholipid syndrome (APS) is a systemic autoimmune disease characterized by thrombotic vascular occlusion and maternal morbidity. Anti-coagulants remain pivotal drugs for the management of APS, but a significant proportion of patients do not benefit from long-term anti-coagulation and may require an alternative therapy to prevent antibody deposition and vascular thrombosis. We have developed a therapeutic approach based on the use of safe polymeric nanoparticles that selectively target beta2-glycoprotein I (β2GPI) deposited on endothelial cells (tNPs). Their efficacy was tested in a rat model of APS developed by infusing patients’ sera containing medium–high titer antibodies against domain I of β2GPI. The tNPs bearing a CH2-deleted anti-β2GPI recombinant antibody as a targeting agent recognize β2GPI deposited on endothelial cells but failed to induce blood clot formation. The tNPs infused into rats immediately before APS sera competed with patients’ antibodies, preventing their binding to deposited β2GPI and, as a consequence, resulted in thrombus formations and occlusion of mesenteric vessels. Similar results were obtained by injecting tNPs 24 hours before the administration of patients’ sera to induce blood clot formation. Our findings suggest that β2GPI-targeted polymeric nanoparticles represent a stable and safe approach to prevent thrombus formation and vessel occlusion in a rat model of APS and may be used to control thrombosis developing in APS patients as a result of acute triggering events.